Assessing the role of small-scale agro-processing projects as a sustainable livelihood strategy in rural communities in Buffalo City Municipality in Eastern Cape, South Africa - Adom, Richard Kwame (My University, 2018)
Post-apartheid South Africa is ranked among many countries in the world with a high degree of income inequality, widespread poverty and high levels of unemployment despite the avalanche of government intervention projects such as agro-processing. Buffalo City Municipality is not immune to this alarming situation. The past two decades have witnessed significant assistance from the Eastern Cape government and Buffalo City Municipality with the intention of promoting an agro-processing strategy coupled with the aim of developing the agriculture sector in the region. The primary aims of agro-processing projects are to increase food production and reduce post harvest losses, thereby reducing food insecurity and poverty. However, these projects in the municipality have not translated into the desired economic growth and development which could cascade into improving the employment and food security in the region. Buffalo City Municipality remains one of the poorest regions in South Africa 21 years after the attainment of democracy. This study, therefore, sought to analyse the role of agro-processing projects about poverty alleviation and sustenance of rural livelihoods. Also, the study identified some of the factors affecting the development of small-scale agro-processing projects in the region. The study collected data using triangulate research methods which consisted of interviews, opened-and close ended questions from the field. Content analysis involving the use of government documents and existing materials from other scholars was relied on as a complementary method to the primary sources in the study. The study concluded that agro-processing projects in the municipality bear relevance in search for sustainable economic growth and development; however, sector departments need to adopt an integrated approach and the value the addition centre concept in promoting the agro-processing business in the municipality.
Research work submitted to the Department of Geography, Archaeology and Environmental Studies in partial fulfilment of the requirements for the degree of Master’s of Science in Geography, University of Witwatersrand, Johannesburg 2018
Keywords: Agricultural processing industries--South Africa; Entrepreneurship--South Africa